2010
DOI: 10.1017/s002211200999245x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and laboratory investigation of breaking of steep two-dimensional waves in deep water

Abstract: The paper extends a pilot study into a detailed investigation of properties of breaking waves and processes responsible for breaking. Simulations of evolution of steep to very steep waves to the point of breaking are undertaken by means of the fully nonlinear Chalikov–Sheinin model. Particular attention is paid to evolution of nonlinear wave properties, such as steepness, skewness and asymmetry, in the physical, rather than Fourier space, and to their interplay leading to the onset of breaking. The role of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 42 publications
3
86
1
Order By: Relevance
“…Babanin et al, 2010), which is what the record shown in Liu et al (2008) and Doong et al (2009) demonstrates. In a quasi-twodimensional wave train with the mean steepness of (3), a wave breaking should develop within approximately 20 wave periods, leading to the wave having individual wave steepness of (Babanin et al, 2007). This is exactly the steepness of the highest wave with H = 32.3 m (1) shown in the record of some 30 waves by Liu et al (2008) and Doong et al (2009).…”
Section: The Measurementssupporting
confidence: 67%
See 1 more Smart Citation
“…Babanin et al, 2010), which is what the record shown in Liu et al (2008) and Doong et al (2009) demonstrates. In a quasi-twodimensional wave train with the mean steepness of (3), a wave breaking should develop within approximately 20 wave periods, leading to the wave having individual wave steepness of (Babanin et al, 2007). This is exactly the steepness of the highest wave with H = 32.3 m (1) shown in the record of some 30 waves by Liu et al (2008) and Doong et al (2009).…”
Section: The Measurementssupporting
confidence: 67%
“…If the modulational instability is active, such steep-in-the-mean waves should develop modulation with a relatively low number of waves in the group (e.g. Babanin et al, 2010), which is what the record shown in Liu et al (2008) and Doong et al (2009) demonstrates. In a quasi-twodimensional wave train with the mean steepness of (3), a wave breaking should develop within approximately 20 wave periods, leading to the wave having individual wave steepness of (Babanin et al, 2007).…”
Section: The Measurementsmentioning
confidence: 73%
“…Babanin et al (2010) showed that interaction of turbulence and bottom stress is also very important.…”
Section: Introductionmentioning
confidence: 99%
“…As it propagates over a plane slope, the wave starts to deform and the wave front moves forward, thus the shape of the wave profile is not symmetric anymore. Several studies have been carried out to investigate the geometric properties of breaking waves in deep water (Babanin et al, 2010;Bonmarin, 1989;Kjeldsen and Myrhaug, 1978;Lader, 2002). Although a considerable amount of literature has been reported on wave steepness and asymmetry factors of shallow water waves (Adeyemo, 1968;Ippen and Kulin, 1954;Iwagaki and Sakai, 1972;Miller and Zeigler, 1964), there have been limited studies on the geometrical asymmetry associated with breaking waves on slopes in shallow water.…”
Section: Introductionmentioning
confidence: 99%